Evaluasi Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (K3) di Rumah Sakit - Vovo, Rahmi; Sari Br Ginting, Yendika Mailina; Hasibuan, Abdurrozzaq (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
The Occupational Safety and Health Management System (SMK3) is an important element in ensuring a safe and healthy work environment, especially in hospitals where there is a high risk to the health and safety of workers and patients. This literature review evaluates the implementation of OSHMS in hospitals based on an analysis of 10 academic journals. The findings show that compliance with regulations, employee training, risk management, and management support are key factors in the successful implementation of SMK3. The use of adequate technology and infrastructure also supports the effectiveness of this system. In addition, a strong safety culture and regular evaluations contribute significantly to improving work safety. Despite challenges such as budget constraints and resistance to change, the benefits of effective implementation of OHSMS include reduced incidents of work accidents, improved employee well-being, and improved quality of health services. This study highlights the importance of a comprehensive approach and ongoing support in implementing OHSMS in hospitals.